Effect of Richardson number on stagnation point flow of double diffusive mixed convective slip flow of magnetohydrodynamic Casson fluid: A numerical study. Issue 6 (23rd November 2021) - Nandeppanavar, Mahantesh M.; Chandrashekhar, Kemparaju M.; Nagaraj, Raveendra
Abstract: An analysis of stagnation point flow of heat and mass transfer of double diffusive mixed‐convective stream with radiating vertical plate and convective boundary conditions. The Runge–Kutta method with shooting procedure is used to solve the transformed equations mathematically. An accuracy of the numerical procedure has been validated through a restriction of the current work compared with prior available results. The shear surface stress, Nusselt and Sherwood number are increased with increase in Prandtl number. The Biot number Bi > 0.1 is investigated and observed that to increase the Prandtl number, the friction coefficient, Nusselt number and Sherwood number are increased. The impact of pertinent constraints on distinct flow parameters are determined and analyzed through tables and graphs.